1999
DOI: 10.1111/j.1439-0531.1999.tb01237.x
|View full text |Cite
|
Sign up to set email alerts
|

Absorption and Synthesis of Immunoglobulins G in Newborn Calves

Abstract: Newborn calves (n=19) got 4.5 liters of pooled colostrum within three feedings in the first 14 hours post natum (p.n.). The immunoglobulin G1 (IgG1) and IgG2 concentrations in the colostrum pool were 54.9 mg/ml and 4.2 mg/ml. The precolostral serum IgG concentrations in calves were 0.15 mg/ml (IgG1; SD 0.24) and 0.06 mg/ml (IgG2; SD 0.14). The highest serum IgG levels p.n. were measured 12 hours after the first colostrum feeding (9.3 mg IgGl/ml (SD 4.0), 0.8 mg IgGl/ml (SD 1.0). Thereafter, the mean IgGl level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
5
1
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 2 publications
4
5
1
2
Order By: Relevance
“…Our study is the first to evaluate passive transfer status in the same individual over the first 10 d of life. The data from this study confirm and expand upon other reports on the decline in concentrations of maternal antibodies in newborn calves after birth, indicating a marked decline occurring around 10 d of age (Erhard et al, 1999;Hassig et al, 2007).…”
supporting
confidence: 90%
See 1 more Smart Citation
“…Our study is the first to evaluate passive transfer status in the same individual over the first 10 d of life. The data from this study confirm and expand upon other reports on the decline in concentrations of maternal antibodies in newborn calves after birth, indicating a marked decline occurring around 10 d of age (Erhard et al, 1999;Hassig et al, 2007).…”
supporting
confidence: 90%
“…Accurate measures of passive transfer of immunity must occur before this onset of active immunity. Also, maternal colostrum IgG has a half-life of approximately 10 d (Erhard et al, 1999;Hassig et al, 2007). Thus, some researchers have suggested that IgG should be measured by 7 d of age (McGuirk and Collins, 2004;Godden, 2008), whereas others have sampled earlier (Villarroel et al, 2013) or as late as 21 d of age (Tyler et al, 1999).…”
mentioning
confidence: 99%
“…BĂĄrta et al (2008) claim an average IgG value for a healthy calf to be 12.74 g/l. In a attempt to Erhard et al (1999) measured a higher average value og the calves 22.5 mg IgG/ml (n = 7, SD = 6.8). This values are little higher than our measurements.…”
Section: Resultsmentioning
confidence: 90%
“…Hal itu sejalan dengan studi sebelumnya oleh jazek et al, (2012) bahwa sapi di usia muda memiliki kadar immunoglobulin lebih rendah dibandingkan dengan usia dewasa. Hal itu dipengaruhi oleh transfer pasif kolostrum pada saat usia muda, sedangkan saat usia dewasa sapi sudah terjadi auto-sintesis immunoglobulin (Erhard et al, 1999). Akan tetapi faktor lain seperti adanya infeksi oleh parasit juga dapat mempengaruhi kadar IgM dan IgG serum sapi (Arlian, 1996).…”
Section: Enzyme Linked Immunosorbent Assayunclassified